Electoral compliance and cultural hegemony: The political economy of elite power in Indonesia’s village governance - M Ridwan Said Ahmad; Jamaluddin Arifin; St. Haniah; Ibrahim Arifin; Risfaisal (Harmoni Sosial: Jurnal Pendidikan IPS, 2026)
Decentralization policies in Indonesia, particularly in Bone Regency, South Sulawesi Province, are often based on the assumption that decentralizing power will destroy traditional hierarchies and promote inclusive governance. However, this study challenges this optimistic view, arguing that without adequate social mechanisms, electoral mechanisms can paradoxically reinforce existing power structures rather than disrupt them. Using political contestation in the Pude Village Head Election as a critical case study, this study analyzes the resilience of feudalism within the framework of modern procedural democracy. Relying on extensive qualitative research, including in-depth interviews and observations of electoral maneuvers, the study explains how “elite fusion” distorts the democratic process. In Pude, local elites represent a powerful intersection of aristocrats, businesspeople, and religious leaders who collaborate to monopolize influence. Analysis shows that these actors exploit deep-rooted cultural doctrines not merely as tradition, but as a hegemonic tool to ensure political compliance. Consequently, patron-client relationships are manipulated to transform voting into an act of cultural obedience rather than rational political choice. Findings reveal that feudal power creates a severe democratic deficit, marked by low transparency, marginalization of non-elite voices, and suppression of genuine contestation. Theoretically, this research expands the literature on “elite capture” and neopatrimonialism by showing that cultural legitimacy is a form of political capital as powerful as economic resources in maintaining dynastic control. The study concludes that institutional reform alone is insufficient to advance substantive democracy; true democratization requires deconstructing feudal dependencies that render citizens subjects rather than empowered voters.